ASSOCIATION ANALYSIS FOR YIELD AND ITS COMPONENTS IN URD BEAN (VIGNA MUNGO L.) GENOTYPES - RAJMOHAN SHARMA (The Bioscan, 2015)
An experiment was conducted during summer and rainy seasons of 2011 and 2012 to estimate the association among yield and its components in urdbean. Correlation coefficient analysis revealed that seed yield per plant exhibited positive and significant association with number of branches per plant (P 0.23, G 0.34 & E 0.16), number of pods per plant (P 0.27, & E 0.36), biological yield per plant (P 0.74, G 0.76 & E 0.72), 100 seed weight (P 0.23, G 0.30 and E 0.20) and harvest index (G 0.40 & E 0.20). Negative association of seed yield per plant was observed with days to maturity and plant height. The characters like number of branches per plant, number of pods per plant, 100 seed weight and harvest index are also positively associated among them indicating the simultaneous improvement of these characters by selection. The study revealed that five characters viz. number of branches per plant, number of pods per plant, biological yield per plant, 100 seed weight and harvest index significantly influence seed yield. Selection of these traits is expected to lead positive results in improvement of seed yield in blackgram.